STRATEGI PEMBERDAYAAN USAHA MIKRO, KECIL DAN MENENGAH (UMKM) DALAM MENGHADAPI GLOBALISASI - Tjutju Fatimah (Fakultas Ekonomi Universitas Negeri Jakarta, 2011)
Abstract Empowerment of Micro, Small and Medium Enterprises is the largest group of economic actors in the Indonesian economy and proved to be a safety valve of the national economy and become dynamist economic growth in addition to being the largest business sector contribution to national development and also create job opportunities so that it is helping to reduce unemployment. Creation of business and investment climate that is conducive to improved governance through institutional Micro, Small and Medium Enterprises and the formulation of policy and its implementation, besides its development program is directed at market-oriented program that is based on considerations of efficiency and the real needs (market oriented, demand-driven program) that will generate sustainable productivity growth. To obtain financing based on the feasibility of revamping and improving the business conducted entrepreneurial skills, organization, management, technical skills of business that was involved, the ability of innovation, financial management. Along the recovery of the banking sector, strengthening the financial sector, particularly banks in providing financing in terms of institutions, products, and financial markets to be able to provide financing with a larger number and type more with the procedures and requirements more easily. Microfinance its existence is necessary for the surrounding communities for consumption or for productive business. Keywords: Micro, Small and Medium Enterprises, Empowerment, Globalization.